A possible contribution of endothelial CCN1 downregulation due to Fli1 deficiency to the development of digital ulcers in systemic sclerosis. Issue 2 (February 2015) - Saigusa, Ryosuke; Asano, Yoshihide; Taniguchi, Takashi; Yamashita, Takashi; Takahashi, Takehiro; Ichimura, Yohei; Toyama, Tetsuo; Tamaki, Zenshiro; Tada, Yayoi; Sugaya, Makoto; Kadono, Takafumi; Sato, Shinichi
Abstract CCN1 is a pleiotropic molecule involved in angiogenesis and postnatal vasculogenesis, both of which are impaired in systemic sclerosis (SSc). To elucidate the potential role of CCN1 in the development of SSc, we investigated CCN1 expression in the lesional skin of SSc patients and SSc animal models and the clinical correlation of serum CCN1 levels. CCN1 expression was markedly decreased in dermal small blood vessels of SSc patients compared with those of healthy controls, while comparable between normal and SSc dermal fibroblasts. Transcription factor Fli1, whose deficiency due to epigenetic suppression is implicated in the pathogenesis of SSc, occupied the CCN1 promoter and gene silencing of Fli1 resulted in the reduction of CCN1 expression in human dermal microvascular endothelial cells. Consistently, CCN1 expression was suppressed uniformly and remarkably in dermal blood vessels of Fli1+/− mice and partially in those of endothelial cell‐specific Fli1 knockout mice. Furthermore, serum CCN1 levels were significantly decreased in SSc patients with previous and current history of digital ulcers as compared to those without. Collectively, these results suggest that endothelial CCN1 downregulation at least partially due to Fli1 deficiency may contribute to the development of digital ulcers in SSc patients. This study further supports the idea that epigenetic downregulation of Fli1 is a potential predisposing factor in the pathogenesis of SSc.